HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP DENGAN PERILAKU KONSUMSI JAJANAN DI MI SULAIMANIYAH JOMBANG - Febryanto, Mukhammad Aminudin Bagus (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyze the relationship between knowledge and attitude with behavior of healthy snack consumption in MI Sulaimaniyah Mojoagung, Jombang.  Methods: This research used quantitative methods. The type of this research was observational and used cross-sectional approach. The dependent variable in this research was the student behavior of snack consumption. And the independent variables were knowledge and student’s attitude. The total population in this research was 86 students. All of them were fifth grades student in MI Sulaimaniyah Mojoagung, Jombang. The sample of this research was 50 students. This research used pearson correlation test to analyzed the results. Results: Most of respondents were 12 years old (64%) and 11 years old (36%) and male (66%). Most of students had known information about nutrient content of food consumption (64%). Most of respondents had a good attitude toward food selection in school (64%). Most of respondents had good behavior of snack’s consumption with positive category (58%). Conclusion: Based on the result of this research, shows there is a relationship between respondents knowledge and attitude with the behavior of healthy snack’s consumption in MI Sulaimaniyah Mojoagung, Jombang in 2016 proven by significant value of 0,000 (p <0,05).